Research on the correlation of immunity in patients with chronic insomnia - Nie, Li; Pan, Xian-li; Zhang, Xiao-bao; Zhang, Shan; Rao, Ji-Xian; Su, Zeng-feng (Frontiers in Psychiatry, 2022)
Purpose:To investigate the changes in immunity and clinical infection events among patients with chronic insomnia. Materials and Methods:Forty-two patients with chronic insomnia (age=64.44±10.53) and 47 normal controls (age=67.08±7.822) were selected to determine differences in data, such as complete blood counts (CBCs), biochemical indices, lymphocyte subsets, immunoglobulin (Ig), complement C3&C4 and interleukin-6 (IL-6), as well as to compare the incidence of clinical infection between the two groups. Results: There were significant differences in erythrocyte, haemoglobin, haematocrit, albumin, globulin, creatinine, IgG, IgG/IgM ratio, CD4+ T-lymphocytes, CD19-lymphocytes, CD4+/CD8+ ratio, platelet/lymphocyte ratio, CD19/CD3 ratio, and clinical infection events between the chronic insomnia group and the control group (p < 0.05). There was no significant difference in neutrophil, lymphocyte, monocyte, and platelet counts; lymphocyte subsets CD8+ T and CD56+; platelet-to-lymphocyte ratio (PLR); neutrophil-to-lymphocyte ratio (NLR); complement C3; complement C4; IgM; IgA; and IL-6 between the experimental group and their controls (p > 0.05). The systolic and diastolic blood pressures of the chronic insomnia group did not vary widely from those of the controls (p > 0.05). Conclusion: Patients with chronic insomnia have immunological abnormalities, characterized by a higher incidence of clinical infection.